Uji Kebisingan pada Motor Listrik dan Tabung Sentifugal Mesin Produksi Santan Kapasitas 10 Liter Per Jam - Herdi Susanto; Al Munawir; Herri Darsan (Jurnal Mekanova: Mekanikal, Inovasi dan Teknologi, 2021)
Noise standards on a machine are very important to consider before the machine is produced, because it can cause discomfort to the operator and damage hearing function. The noise standard has been set by OSHA, the maximum noise threshold value of 85 dB is considered safe for most workers when working 8 hours / day. The coconut milk production machine with a capacity of 10 liters per hour was carried out by measuring the noise level which aims to determine whether the machine meets the noise standard criteria. The test was carried out at three levels of motor rotation, namely 1000 rpm, 1500 rpm, 2000 rpm with a noise measuring distance of 0.5 meters from the component parts of the electric motor and centrifugal tube using a sound level meter. The results of measurements of noise levels on electric motors and centrifugal tubes of coconut milk production machines with a capacity of 10 liters per hour can be concluded that the noise level value of the production machine meets the noise standard level required by OSHA 1978, where the maximum production machine noise level is at 75 dB while that which is implied by OSHA 1978 maximum is at 85 dB. Keywords— OSHA standards, electric motor, centrifugal tube, noise test